Hepatoprotective Activity of Ethanolic Extract of Sida rhombifolia L. Leaf in CCl4-induced Rats - Nisa Isneni Hanifa; Wahyu Widyaningsih (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2020)
Streptococcus mutans is responsible for cause the dental caries. The purpose of this research was to test antibacterial activity of Ganitrus leaves. The bacterial activity of methanol and aquadest by disc difusion method with 10%; 20%; 30%; 40%; 50% and 100%. The extracts showed that methanol extract had activity with susceptible category at concentration of 10%, 30%, 50% and 100% against Streptococcus mutans with inhibition zone 15.74mm, 16.68 mm, 16.70 mm and 17.68 mm, respectively. Aquadest extract showed activity with intermediet category of 30% and 100% with inhibition zone 11,04 mm and 11,39 mm. The methanol extract showed that activity of antibacterial better than the aqueous Elaeocarpus ganitrus Roxb leaves.